Bridging the Brain–Body Divide: A Commentary and Response to Wilkinson. Issue 2 (9th July 2019) - FIELD, THOMAS A.
Abstract: In response to Wilkinson's (2018) critique of humanistic counseling's alliance with neuroscience, the author explores the concept of the brain–body divide, proposes an adjustment to Wilkinson's quadripartite model, and suggests ways for humanistic counselors to integrate levels of consciousness and the brain–body connection into their work with clients.